Abordagem do descarte de lixo eletrônico no Programa Unidos em Prol do Meio Ambiente (PUMA) em Ilha Solteira/SP - Morais, Gabriela Noronha [UNESP] (2015)
The Programa Unidos em Prol do Meio Ambiente (PUMA) is a result of an anual project envolving the groups PET Mechanical Engineering from Ilha Solteira/SP and PET Pharmacy from Araraquara/SP, that a subject related to enviroment is approached whit childs in their own cities. This year the subject chosen was “disposal of solid waste”, wherein PET's Mechanical Engineering focus is eletronical waste and PET's Pharmacy ones is medicine waste, both elaborate with sudents from 5th year of elementary school in three steps.